A mitochondrial genome phylogeny of Mytilidae (Bivalvia: Mytilida) - Lee, Yucheol; Kwak, Haena; Shin, Jinkyung; Kim, Seung-Chul; Kim, Taeho; Park, Joong-Ki (Molecular phylogenetics and evolution, 2019)
[Display omitted] •The phylogenetic relationships among subfamilies of the Mytilidae are uncertain.•A mitochondrial genome phylogeny was reconstructed for 27 mytilid species.•The phylogeny shows two major clades that have diverged in the Devonian.•The splitting time among the major subfamilies occurred in the Mesozoic period. The family Mytilidae is a family of bivalve mussels that are distributed worldwide in diverse marine habitats. Within the family, classification systems and phylogenetic relationships among subfamilies remain not yet fully resolved. In this study, we newly determined 9 mitochondrial genome sequences from 7 subfamilies: Bathymodiolus thermophilus (Bathymodiolinae), Modiolus nipponicus (Modiolinae), Lithophaga curta (the first representative of Lithophaginae), Brachidontes mutabilis (Brachidontinae), Mytilisepta virgata (Brachidontinae), Mytilisepta keenae (Brachidontinae), Crenomytilus grayanus (Mytilinae), Gregariella coralliophaga (Crenellinae), and Septifer bilocularis (the first representative of Septiferinae). Phylogenetic trees using maximum likelihood and Bayesian inference methods for 28 mitochondrial genomes (including 19 previously published sequences) showed two major clades with high support values: Clade 1 ((Bathymodiolinae + Modiolinae) + (Lithophaginae + Limnoperninae)) and Clade 2 (((Mytilinae + Crenellinae) + Septiferinae) + Brachidontinae). The position of the genus Lithophaga (representing Lithophaginae) differed from a previously published molecular phylogeny. Divergence time analysis with a molecular clock indicated that lineage splitting among the major subfamilies of Mytilidae (including the habitat transition from marine to freshwater environments by ancestral Limnoperninae) occurred in the Mesozoic period, coinciding with high diversification rates of marine fauna during that time. This is the first mitochondrial genome-based phylogenetic study of the Mytilidae that covers nearly all subfamily members, excluding the subfamily Dacrydiinae.